United Kingdom : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for United Kingdom. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that economic growth in the United Kingdom has turned sharply negative since mid-2008. Housing prices have fallen by more than 20 percent from their peak, the unemployment rate has increased, and inflation has come down. In response to the crisis, the authorities have taken wide-ranging measures to stabilize the financial system and support demand. Executive Directors have stressed that the most important policy task remains repairing the financial system. Directors have also welcomed the adoption of the Special Resolution Regime for financial institutions.